Reconstruction of The Vice Regent’s Position in Optimization of Regional Autonomy: Realizing Democratic and Justice Values - Palullungan, Liberthin; Lumentut, Lisma; Ayub, Zainal Amin (Magister of Law, Faculty of Law, University of Mataram, 2023)
The ambiguity of the Deputy Regent's position in local government makes the Deputy Regent's position often underestimated. The Deputy Regent is perceived as a subordinate of the Regent even though the Regent and Deputy Regent are both directly elected by the people. This study aims to reconstruct the Deputy Regent's position in order to optimize regional autonomy while at the same time embodying the values ​​of democracy and justice. This research is doctrinal research, prioritizing conceptual and statutory approaches. The results of the study confirmed that the weak position of the Deputy Regent compared to the Regent in carrying out his duties was caused by two factors, namely the juridical factor in the form of the absence of special arrangements regarding the duties and powers of the Deputy Regent, and from non-juridical factors, which is a political factor that placed the Deputy Regent as the Regent's subordinate. Efforts to realize the values ​​of democracy and justice for optimizing regional autonomy can be carried out by reconstructing the authority of the Deputy Regent by strengthening the proportional distribution of authority between the Regent and Deputy Regent.